2007
DOI: 10.1002/bmb.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a bioinformatics across life science curricula initiative

Abstract: At the University of Wisconsin-La Crosse, we have undertaken a program to integrate the study of bioinformatics across the undergraduate life science curricula. Our efforts have included incorporating bioinformatics exercises into courses in the biology, microbiology, and chemistry departments, as well as coordinating the efforts of faculty within those departments. Here, we assess student confidence in solving and ability to solve bioinformatics-related problems. Assessment data show increases in student perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…(2006), Howard et al . (2007), Wefer and Anderson (2008), and McEwen et al (2009), all used multiple assessments to measure their presumptive constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2006), Howard et al . (2007), Wefer and Anderson (2008), and McEwen et al (2009), all used multiple assessments to measure their presumptive constructs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the articles by Chapman et al . (2006), Howard et al . (2007), and Wefer and Anderson (2008) used cross-validation to provide convergent external validity evidence.…”
Section: Discussionmentioning
confidence: 99%
“…What can NIBLSE and other such groups do to facilitate solutions? Although there are several institutions that have successfully integrated bioinformatics into their life science programs (20), including University of Wisconsin-La Crosse (21), Kalamazoo College (22), Muhlenberg College (23), and Drake University (24), the vast majority of institutions appear not to have done so. Clearly, given that we and others (16,25) have found that lack of faculty training is a major problem, providing faculty with opportunities for training is important, as is giving faculty time to take advantage of these opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Educators have responded by incorporating bioinformatics into diverse life science curricula [42]–[44]. While these published exercises in, and guidelines for, bioinformatics curricula are helpful and inspirational, faculty new to the area of bioinformatics inevitably need training in the theoretical underpinnings of the algorithms [45].…”
Section: Introductionmentioning
confidence: 99%